Identifikasi Penalaran Kreatif-Imitatif Siswa dengan Gaya Kognitif Reflektif - Durrotun Nabilah; Ismail; Elly Matul Imah (LP. Ma'arif Janggan Magetan, 2023)
This research is aimed to describe the creative and imitative reasoning of students with reflective cognitive styles on math problem solving. The study uses a qualitative approach with a data collection instrument used of Matching Familiar Figure Tests, math ability test, mathematical problem-solving tasks, and interview guidelines. The research result studies indicate that a student with reflective cognitive style that have imitative reasoning in problem solving is less able to provide comprehensive information, still using a problem-solving strategy previously known, nor does he make a return check on the results received. It is different with reflective subjects that have proven creative reasoning capable of delivering well-known information, that can provide novel and thought-provoking solutions. Moreover, he also looking back the resulting solutions to the problem.